Analisis Peran Ganda Single Parent Dalam Pendidikan Anak Di Desa Sukomulyo Manyar Gresik - Mufidah, Lailatul; Hidayati, Roziana Ainul (Jurnal Mahasiswa Manajemen, 2022)
The high divorce rate every year in the Gresik area, resulting in many women with single parent status who have multiple roles. Divorce makes the family less qualified and has an impact on the human resources produced, which also decreases. Most children of single parent women have poor quality education. This study aims to analyze how to play a dual role with single parent status in children's education in Sukomulyo Manyar Gresik Village. This type of research is qualitative research. The selection of informants in this study, researchers conducted interviews with 5 (five) single parents, using purposive sampling with several criteria. Data collection techniques used are observation and interviews. Data analysis uses data reduction, data presentation and conclusion drawing. The data validation technique uses member check. The results of this study indicate that someone who carries out multiple roles with single parent status has very little free time with children. Busy parents work all day resulting in less concern for children in learning activities, but it does not reduce the enthusiasm for single parent women to motivate and encourage their children to realize their future. This research contributes to single parents in order to provide knowledge about the dual roles they face in supporting their child's educational development. This research was only conducted on single parent women who play multiple roles in the Village of Sukomulyo Manyar Gresik